Leibniz's Law and Identity - Dowling, William Keith (My University, 1970)
In this essay I consider various alleged exceptions to the principle of the indiscernibility of identicals -- Leibniz's Law. There are two major difficulties. First, the apparent antinomy that arises when Leibniz's rule combines with the modalities. I argue that there are a number of ways of dealing with this problem and we are not therefore obliged-to abandon or modify Leibniz's rule. Second, the unacceptable inference which results when Leibniz's rule is applied in contexts expressing mental attitudes. Here, I show how Leibniz's rule and intentional attitudes combine in a perfectly acceptable way.
I also deal with a number of other minor objections to this rule, from the current literature on the topic, all of which I hope to show present no difficulties. In fine, despite the many apparent counter-examples considered, I hope to show Leibniz' s Law, which permits the unrestricted interchange of the terms of an identity sentence, has not been falsified.
Keywords: Philosophy; Philosophy